Variability in water use efficiency at the leaf level among Mediterranean plants with different growth forms - Medrano, Hipólito; Flexas, Jaume; Galmés, Jeroni (Plant and soil, 2009)
Assessing natural variability of leaf water use efficiency in plants adapted to extreme conditions of the Mediterranean climate represents an important step in the evaluation of the usefulness of some plant ecophysiological traits under water stress. Eleven Mediterranean species naturally inhabiting the Balearic Islands and corresponding to different growth forms (herbs, semi-deciduous shrubs, woody evergreen shrubs and woody evergreen semi-shrubs) were subject to progressive soil water depletion. Leaf intrinsic water use efficiency was measured by gas exchange at four different degrees of water stress. Under well watered conditions, differences in leaf intrinsic water use efficiency (A N/g s) among growth forms were limited to woody evergreen semi-shrubs, which presented the highest values. Under water stress conditions, differences became more evident, with a trend for an increase in A N/g s from woody evergreen shrubs, through semi-deciduous shrubs and herbaceous to woody evergreen semi-shrubs. The observed variation in A N/g s correlated with several physiological (leaf water potential, soil to leaf hydraulic conductance and stomatal conductance) and morphological (stomatal density) parameters, displaying a general relationship for all growth forms. This suggests that the capacity for withstanding water limitation is adaptive for all Mediterranean species. However, when A N/g s was related to leaf mass area, this relationship was not generally applicable, and depended on growth forms, suggesting that different growth forms display specific morphological adjustments in response to water shortage.